RESEARCH OF THE MAIN ASPECTS OF INNOVATIVE POLICY OF THE ENTERPRISE IN THE DOMESTIC INDUSTRY - T. Barsova (Publishing House of the State University of Management, 2017)
The article is devoted to topical issues related to improving the innovative activity in the industry. In particular, at the enterprises of machine-building complex. The introduction of modern innovation policy could be one of the most effective factors of economic growth in this sector of the economy. The authors explain the role of innovation policy, its basic goals and objectives, and presents a modern interpretation of the classification of innovations.